Implementation of Heart Rate System using AD8232 and Arduino Microcontrollers - Setiawan, Muhammad Haryo; Sari, Nurjanah Arvika; Prasetya, Wahyu Latri; Feter, Muslih Rayullan; Saputra, Dodi; Ma'arif, Alfian (Signal and Image Processing Letters, 2020)
The human heart's pivotal role in maintaining overall health by ensuring oxygen and nutrient delivery to tissues and waste elimination highlights the global importance of cardiac health. Electrocardiography (ECG) is a fundamental tool for assessing cardiac conditions, capturing intricate electrical signals during each heartbeat. ECG sensors are instrumental in this process, finding extensive applications in personal health monitoring, disease management, and medical research. This article emphasizes the significance of ECG sensors, particularly the AD8232 ECG sensor paired with the Arduino Nano microcontroller. It outlines their operational principles, measurement methods, and signal-processing techniques. The research aims to enhance the accuracy and efficiency of ECG data capture, contributing to advanced cardiac monitoring systems. Intelligent systems employing biopotential sensors and electrocardiographs enhance diagnostic precision, minimizing interpretational errors. ECG sensors, which record and translate the heart's electrical activity into interpretable data, are integral to modern medicine. They are used in diverse settings, from clinical environments to personal health monitoring. Ensuring ECG sensor accuracy is critical, as the data directly impacts diagnosis and treatment. This article offers insights into fundamental principles, measurement procedures, and programming techniques for ECG sensors, facilitating efficient data capture and processing. These findings promise user-friendly cardiac monitoring systems advancements, significantly contributing to medical technology and healthcare.